The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1021/j100013a067
|View full text |Cite
|
Sign up to set email alerts
|

Connection between Structure, Electronic Spectrum, and Electron-Transfer Properties of Blue Copper Proteins

Abstract: The connections between site structure, electronic structure and spectra, and electron-transfer properties of type 1 or blue copper proteins are investigated. The theoretical model includes the nearest neighbors of the Cu ion and the residues to which these neighbors are attached. The electronic structure is calculated using an extended CNDO/S method adapted to spin doublet states. The calculated spectra agree reasonably well with the experimental ones as well as with the calculations of Solomon et al. The str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
102
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(115 citation statements)
references
References 12 publications
13
102
0
Order By: Relevance
“…Larsson et al have reported semiempirical CNDO/S calculations of the active site of azurin. 20 An intense band was predicted to lie at 13 800 cm À1 , and in agreement with Solomon was assigned to excitations from the bonding Cu 3d-S cys 3p p orbital. Contrary to the earlier work, ligand field excitations were found at higher energy.…”
Section: Introductionsupporting
confidence: 61%
“…Larsson et al have reported semiempirical CNDO/S calculations of the active site of azurin. 20 An intense band was predicted to lie at 13 800 cm À1 , and in agreement with Solomon was assigned to excitations from the bonding Cu 3d-S cys 3p p orbital. Contrary to the earlier work, ligand field excitations were found at higher energy.…”
Section: Introductionsupporting
confidence: 61%
“…8 Semiempirical electronic-structure calculations have indicated, however, that little charge redistribution actually occurs in this transition, so this characterization may be misleading. 9,10 The weaker peak at 770 nm is a combination of three transitions from filled copper d orbitals to the half-filled d 11 The most widely studied blue copper protein is plastocyanin, a small (10.5 kDa) photosynthetic protein of plants, algae, and cyanobacteria that transfers an electron from cytochrome f in photosystem II to a chlorophyll in photosystem I. 12 Although a plastocyanin protein contains a single copper center, many proteins in this class contain several copper atoms, some of which may not be bound to active sites of the blue type I configuration.…”
Section: Introductionmentioning
confidence: 99%
“…17a The fact that most of the resonance-enhanced modes involve the Cu-S(cysteine) stretch can be rationalized from the results of semiempirical calculations, which show that the electronic excitation is localized around this bond. 9,10 Thus, it is expected that this bond will undergo the most distortion upon excitation. 16 Solomon et al have suggested that the Cu-S(cysteine) bond plays a key role in the physiological electronic-transfer event.…”
Section: Introductionmentioning
confidence: 99%
“…Plastocyanin indicates intense absorption band due to the S Cys 3 Cu(II) charge transfer at visible region and a narrow hyperfine coupling constant in the EPR spectra of the oxidized form (2). The electronic structure of plastocyanin has been reported by several groups (3)(4)(5). Solomon and co-workers (6) gave an implication for the electron transfer reaction mechanisms on the basis of the electronic structure of plastocyanin.…”
mentioning
confidence: 99%